The Role of Ismuba Teachers in Character Building in One of the Elements of the Pancasila Student Profile at SMK Muhammadiyah 8 Pakis - Nanang Zakaria; Abdul Haris (Penerbit Hellow Pustaka, 2024)
The Pancasila student profile aims specifically to train and shape students to achieve competencies in line with the expectations of the Indonesian education system. The main focus of this profile is to ensure that every student not only deeply understands the values of Pancasila but also internalizes and applies them in daily life. Thus, the Pancasila student profile does not solely pursue academic achievement but also aims to shape students' character in accordance with the moral, social, and ethical values expected by the national education system. Through this approach, it is expected that students will be able to become positive contributors to society and be aware of their moral responsibilities in living within the community. The Pancasila student profile aims to produce students who meet the competencies of the Indonesian education system. This study uses a qualitative descriptive case study approach to describe the role of ISMUBA teachers in their efforts to strengthen the Pancasila student profile through ISMUBA learning at SMK Muhammadiyah 8 Pakis. The results of the study indicate that the implementation of ISMUBA has successfully instilled character in one of the elements of the Pancasila student profile, namely, being faithful and pious to God Almighty and having noble character. This method not only creates a positive learning environment but also shapes students' essential character and skills to face the modern world.